Effect of Fe and Al ions on the production of biochar from agricultural biomass: Properties, stability and adsorption efficiency of biochar. (July 2021) - Han, Lanfang; Sun, Haoran; Sun, Ke; Yang, Yan; Fang, Liping; Xing, Baoshan
Abstract: In recent years, researchers have sought ways to efficiently convert biomass wastes into biochars with potential for environmental application. Fe and Al salts are reactive constituents that participate in biochar formation. However, their influences on the properties of biochar and its application on contaminant removal and carbon mitigation remain unknown. In this study, FeCl3 and AlCl3 were added to two typical biomass wastes (rice straw and poultry litter) during pyrochar and hydrochar production. The effects of Al (Ⅲ) and Fe (Ⅲ) on the molecular characteristics, stability, and adsorption efficiency of biochars for polar and nonpolar contaminants were explored. Results showed that Al (Ⅲ) and Fe (Ⅲ) significantly changed the properties of biochar. Al (Ⅲ) facilitated the carbonization of 250 °C pyrochar, but suppressed that of hydrochar and 450 °C pyrochar. Fe (Ⅲ) enhanced the formation of aromatic structures of both pyrochar and hydrochar, but reduced the abundance of lignin- and condensed aromatics-like species in their dissolved organic carbon fractions. Furthermore, Fe (Ⅲ) increased the stability and adsorption efficiency of pyrochar and hydrochar for both polar and nonpolar contaminants. These findings provide new insights into the design of functional biochar from biomass wastes with high stability and adsorption efficiency for organic contaminants. Highlights: Al (Ⅲ) and Fe (Ⅲ) were added to biomass during pyrochar and hydrochar production. Effect of Al (Ⅲ) on thermal conversion of biochar depended on pyrolysis conditions. Fe (Ⅲ) enhanced the formation of aromatic structure of both pyrochar and hydrochar. Fe (Ⅲ) improved the stability and adsorption efficiency of biochar.